THE ACTION OF CHLORINATED ANTISEPTICS ON BLOOD CLOT - Taylor, Herbert D. (The Rockefeller University Press, 1919)
This work demonstrates that the chlorinated antiseptics have no power to penetrate blood clots and destroy bacteria therein contained. Correspondingly, blood clots may protect virulent bacteria for a long period of time and the organisms properly planted will be able to proliferate in a normal manner.